ELLORA: Enabling Low Resource Languages with Technology - Bali, Kalika; Choudhury, Monojit; Sitaram, Sunayana; Seshadri, Vivek (UNESCO International Conference on Language Technologies for all (LT4All), 2019)
Language technology has had a huge impact on the way language communities communicate and access information. However, this revolution has bypassed over 5000 languages around the world that have no resources to develop technology in their languages. ELLORA, with its mission to empower every person and every organization using underserved languages to achieve more, is a program for enabling low resource languages through language technology. In this paper we describe how through innovative methodologies and techniques that allow systems to be built in resource constrained settings, ELLORA seeks to positively impact the underserved language communities around the globe.